The Relationship Digital Literation on Sustainability Report Disclosure : Case in Indonesia Company listed Stock Exchange Market - Nanik Sri Utaminingsih; Alan Dharma Saputra; Indah Fajarini Sri Wahyuningrum (ITB AAS Indonesia, 2025)
Sustainability reports are reports that contain corporate responsibility in economic, social and environmental aspects. The purpose of this study is to empirically examine the determinant factors that influence the disclosure of sustainability reports. This study examines the effect of company size, profitability, social media, and industry type on sustainability report disclosure. This study used a sample of 128 manufacturing companies with a total of 284 units of data analysis. This research is a quantitative study that uses secondary data. In the research method used descriptive and inferential analysis through panel data regression analysis and moderated regression analysis (MRA) using Eviews 12 software. The results showed that profitability and social media have a positive and significant effect on sustainability report disclosure. Company size has no effect on sustainability report disclosure. Furthermore, the type of industry as a moderating variable is not able to strengthen the influence between independent variables on sustainability report disclosure.